Analysis and research of government procurement audit in universities based on big data environment. (17th February 2018) - Zhang, Fan; Zhang, Yan; Yuan, Haizhao; Gao, Mengmeng; Zhang, Jingjing
Abstract: According to problems existing in the process of university audit informatization, the internal audit framework based on big data is analyzed in this paper. Audit data processing and analysis technology of government procurement in universities based on big data are elaborated. Analysis models of the government procurement audit that highlight the association analysis are established, and through the government procurement audit data, the validity of the models is verified. The researches in the paper can provide an important reference for auditing department, and also can promote the improvement of government procurement system and the level of management authority.